ENDOSCOPIC CHANGES RELATED TO GASTROESOPHAGEAL REFLUX DISEASE: COMPARATIVE STUDY AMONG BARIATRIC SURGERY PATIENTS - SANTO,Marco Aurelio (2015)
Background : Obesity is correlated with several comorbidities, including gastroesophageal reflux disease. Its main complications are detectable by endoscopy: erosive esophagitis and Barrett's esophagus. Aim : To correlate erosive esophagitis and hiatal hernia with the degree of body mass index (BMI). Method : Was performed a retrospective analysis of 717 preoperative endoscopic reports of bariatric patients. Fifty-six (8%) presented hiatal hernia, being 44 small, nine medium and five large. Esophagitis was classified by Los Angeles classification. Results : There was no correlation between the presence and dimension of hiatal hernia with BMI. One hundred thirty-four (18.7%) patients presented erosive esophagitis. Among them, 104 (14.5%) had esophagitis grade A; 25 (3.5%) grade B; and five (0.7%) grade C. When considering only the patients with erosive esophagitis, 77.6% had esophagitis grade A, 18.7% grade B and 3.7% grade C. Were identified only two patients with Barrett's esophagus (0,28%). Conclusion : There was a positive correlation between the degree of esophagitis with increasing BMI.